Penerapan Kompres Hangat Terhadap Skala Nyeri Dismenore pada Remaja Putri di Desa Tanjung Sukoharjo - Clariza Nugraheni Dian Puspitasari; Eska Dwi Prajayanti (Jurnal Anestesi, 2024)
Dysmenorrhea is menstrual pain in the lower abdomen that radiates to the waist and is accompanied by a headache that lasts for seven days due to increased production of prostaglandins and their release from the endometrium during menstruation. The prevalence of adolescent girls in Indonesia who experience dysmenorrhea is 64.25% which consists of primary dysmenorrhea 54.89% and secondary dysmenorrhea 9.36%. Warm compress is one of the non-pharmacological therapies that can be used to reduce dysmenorrhea pain. Describe the results of the comparison of the dysmenorrhea pain scale before and after warm compresses. This application uses a descriptive case study method on 2 respondents with dysmenorrhea pain. Performed once a day for 2 days with a time of 30 minutes. The instruments used in this application are (Warm Water Zak) WWZ, thermometer, hot water and measurement using (Numeric Ratting Scale) NRS. There was a decrease in dysmenorrhea pain in both respondents after being given a warm compress on Ms. A from a scale of 6 to 2 and on a Numeric Ratting Scale. A from scale 6 to 2 and on Ms. I from scale 5 to 3. I from scale 5 to 3. Conclusion: The application of warm compress therapy can reduce the dysmenorrhea pain scale in both respondents.